Procjena prognostičkog rizika smrti u bolesnika s višestrukom mielomom baziranom na CD184 i CD269: retrospektivna analiza - Chen, Hong; Zhao, Yuan; Zhang, Zhiyu; Xie, Yan; Jin, Mulan (Journal of Medical Biochemistry, 2025)
Background: This study aimed to analyze the expressions of CD184 and CD269 in patients with newly diagnosed multiple myeloma (MM) in China and explored their potential association with prognosis.Methods: This retrospective study recruited 100 patients with MM and 113 healthy controls who attended Beijing Chaoyang Hospital Shijingshan District between June 2020 and December 2023. The association between CD184 and CD269 expression and patient survival outcomes was assessed using univariable and multivariable Cox proportional hazards regression analyses, alongside Kaplan-Meier survival curves.Results: Both CD184 and CD269 mRNA were elevated in MM patients compared to controls (P